2013
DOI: 10.1063/1.4774042
|View full text |Cite
|
Sign up to set email alerts
|

An atomic layer deposition reactor with dose quantification for precursor adsorption and reactivity studies

Abstract: An atomic layer deposition reactor has been constructed with quantitative, precision dose control for studying precursor adsorption characteristics and to relate dose quantity and exposure dynamics to fluid flow in both the viscous and molecular flow regimes. A fixed volume of gas, held at a controlled temperature and measured pressure, is dosed into the reaction chamber by computer-controlled pneumatic valves. Dual in situ quartz crystal microbalances provide parallel mass measurement onto two differently coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…This contrast in growth rate and uniformity dependence on t TMA‑pulse vs t H 2 O‑pulse suggests that TMA vapor is more quickly chemisorbed and efficiently consumed as a complete monolayer as it flows through the chamber, which can be defined as a mass transport-limited reaction, but H 2 O vapor is slowly consumed and more likely to pass over all chamber surfaces before being chemisorbed, which can be defined as a surface reaction-limited process. These observations in large-area AlO x growth rate and uniformity dependence on TMA and H 2 O pulse times confirm the common understanding that the TMA half-reaction behaves more ideally in the formation of a self-limited monolayer than the H 2 O half-reaction, which is more prone to temperature-sensitive surface reactions resulting in uniformly sparse monolayers or adsorption greater than a monolayer. …”
Section: Resultssupporting
confidence: 77%
“…This contrast in growth rate and uniformity dependence on t TMA‑pulse vs t H 2 O‑pulse suggests that TMA vapor is more quickly chemisorbed and efficiently consumed as a complete monolayer as it flows through the chamber, which can be defined as a mass transport-limited reaction, but H 2 O vapor is slowly consumed and more likely to pass over all chamber surfaces before being chemisorbed, which can be defined as a surface reaction-limited process. These observations in large-area AlO x growth rate and uniformity dependence on TMA and H 2 O pulse times confirm the common understanding that the TMA half-reaction behaves more ideally in the formation of a self-limited monolayer than the H 2 O half-reaction, which is more prone to temperature-sensitive surface reactions resulting in uniformly sparse monolayers or adsorption greater than a monolayer. …”
Section: Resultssupporting
confidence: 77%
“…53,56 The GPC for ALD is affected by various process parameters, such as the growth temperature, 53 pressure of reactants, 53,57 exposure time of precursors and reactants, 53 and reactor design. 58 For example, varying the working pressure changed the gas flow rate near the surface, which in turn changed the sticking probability on the surface, leading to a change in the GPC. 56 A previous study reporting the ALD Al 2 O 3 process for working pressures of 2 and 760 Torr, found a wide range in the growth per cycle (0.9−1.7 Å/cycle).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The growth per cycle (GPC) in the ALD Al 2 O 3 process is about 1.6 Å/cycle. The generally reported growth per cycle values for ALD Al 2 O 3 using TMA and H 2 O are about 0.9–1.7 Å/cycle. , The GPC for ALD is affected by various process parameters, such as the growth temperature, pressure of reactants, , exposure time of precursors and reactants, and reactor design . For example, varying the working pressure changed the gas flow rate near the surface, which in turn changed the sticking probability on the surface, leading to a change in the GPC .…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Increasing the sulfur content in Zn(O,S) raises the conduction band energy, which is critical in adjusting the conduction band offset (CBO) at the buffer/absorber interface to optimize the solar cell device performance, 13 as illustrated for SnS/Zn(O,S) heterojunctions in Fig. S1 (see Ref.…”
mentioning
confidence: 99%